Reisolasi dan Identifikasi Fungi pada Batang Gaharu (Aquilaria malaccencis Lamk.) Hasil Inokulasi. - Lisdayani Lisdayani; Nelly Anna; Edy Batara Mulya Siregar (Program studi Kehutanan USU, 2015)
Gubal of Agarwood is the infection of the microorganism and one of commonly used is Fusarium sp. The purpose of this research was to determine the presence of Fusarium sp consistency in agarwood (Aquilaria malaccencis Lamk.) which has been in the fungal inoculation.Sample which to used is stem which is taken away from Penungkiran Durin Jangah village, Pancur Batu. Isolation and identifying has been done in Forest Biotechnology laboraturium of Agriculture faculty University of Sumatera Utara, which is conducted from April – October 2013. The result of this research showed that there are fifteen isolat of fungi from the stem, that are five isolat Fusarim sp, two isolat Acremonium sp, two isolat Alternaria alternaria, one isolat Nigrospora sphaerica, two isolat Scopulariopsis sp, two isolat Cladosporium sp, one isolat Scytalidium lignicola, one isolat Mucor sp. Consistency Fusarium sp are superior on top stem and all of the part of the stem can be found Fusarium sp.Keywords: fungi, Agarwood, Reisolation, consistency